Isolamento e caracterização da lectina camptosemina extraída das sementes de Camptosema ellipticum - Batista, Fernanda Aparecida Heleno (Universidade Federal de São Carlos, 2007)
Lectins are (glico) proteins of non immune origin able to cause cellular agglutination or precipitation of glicoconjugates. Legume lectin refers to plant lectins that are found exclusively in species of the Leguminosae family. A notable characteristic of legume lectins is that all their proteins share tertiary structure consisting of a jelly-roll motif, which is basically composed by β sheet, but present great variability the quaternary association. This variability is considered responsible for conferring different degrees of stability to the legume lectins. This work presents the isolation and characterization of the camptosemin, a protein of legume lectins family, isolated from seeds of Camptosema ellipticum, a plant that belongs to the Brazilian open pasture. Camptosemin found to be a tetrameric protein, whose protomers exhibits approximately 26 kDa. It was able to agglutinate erythrocyte of all ABO sanguineous types and it was showed high affinity for N-acetylgalactosamin carbohydrate. Spectroscopic assays have demonstrated that camptosemin is an extremely resistant protein against the thermal and chemical unfolding. Through the analysis of the unfolding curves and the refolding assays, a model of two states for the unfolding of the protein was proposed. According to this model, at the equilibrium, only presents native tetramers and unfolded monomers. The obtained values of Tm and are in agreement with the ones described for other lectins. G O H Δ 2
Keywords: Proteínas - caracterização; Lectinas; Camptosemina; Camptosema ellipticum; Dicroísmo circular; Fluorescência; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS